Etika Kerja sebagai Perwujudan Ideologi Kapitalisme dalam Novel Mercy Street Karya Mariah Stewart - Yulistiyanti Yulistiyanti (Universitas Stikubank (UNISBANK) Semarang, 2013)
This article discusses on popular fiction entitled Mercy Street by Mariah Stewart. Itapplies ideology theory by Louise Althusser and capitalism ideology by MaxWeber. Althusser discusses ideology which consists of representation,existence, and practice. Moreover, Weber argues on capitalism ideology which isimplied in daily life. It constructs work ethic. The work ethic derived fromcapitalism ideology are discipline, work hard, frugality, honesty andindividualism. Characters of the fiction conduct the ethics in their life whichthe author creates. Keywords: popular fiction, ideology, capitalism, Mercy Street, Mariah Stewart